2013
DOI: 10.1371/journal.pone.0078942
|View full text |Cite|
|
Sign up to set email alerts
|

Changing Use of Surgical Antibiotic Prophylaxis in Thika Hospital, Kenya: A Quality Improvement Intervention with an Interrupted Time Series Design

Abstract: IntroductionIn low-income countries, Surgical Site Infection (SSI) is a common form of hospital-acquired infection. Antibiotic prophylaxis is an effective method of preventing these infections, if given immediately before the start of surgery. Although several studies in Africa have compared pre-operative versus post-operative prophylaxis, there are no studies describing the implementation of policies to improve prescribing of surgical antibiotic prophylaxis in African hospitals.MethodsWe conducted SSI surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…Eight studies evaluated bundles combining different interventions. 36 43 A cluster randomized controlled trial in eight Kenyan hospitals compared a bundle containing guidelines, education and face-to-face feedback to prescribers with a similar, but less intensive bundle (fewer hours of training, written feedback; Table 2 ). 37 Comparing prescriptions for 594 children in intervention hospitals and 566 children in control hospitals showed that the intensive bundle was associated with a non-significant absolute risk reduction in inappropriate use of antibiotics for non-bloody diarrhoea of 41% (95% CI: −6 to 88%).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies evaluated bundles combining different interventions. 36 43 A cluster randomized controlled trial in eight Kenyan hospitals compared a bundle containing guidelines, education and face-to-face feedback to prescribers with a similar, but less intensive bundle (fewer hours of training, written feedback; Table 2 ). 37 Comparing prescriptions for 594 children in intervention hospitals and 566 children in control hospitals showed that the intensive bundle was associated with a non-significant absolute risk reduction in inappropriate use of antibiotics for non-bloody diarrhoea of 41% (95% CI: −6 to 88%).…”
Section: Resultsmentioning
confidence: 99%
“…What is currently being done to address SAP internationally? Successful interventions to improve SAP prescribing include studies in both resource limited and resource rich settings, and include the collaborative development of guidelines, data collection on compliance with guidelines and quality assurance cycles with audit and direct prescriber feedback [7,[9][10][11]. However, in both contexts suboptimal SAP prescribing persists, and barriers to implementation are evident, including the enduring belief within surgery regarding the benefit of post-operative SAP administration to prevent SSI [10,12,13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, different results were reported from the Netherlands (50%) and Nicaragua (22%) . A study conducted in Africa also found that > 99% of surgical patients received the first dose of SAP after the end of the surgical procedure . If the prophylaxis is started at the wrong time, the patients will have inadequate serum and tissue concentrations of antibiotic at the time of incision and during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…18 A study conducted in Africa also found that > 99% of surgical patients received the first dose of SAP after the end of the surgical procedure. 19 If the prophylaxis is started at the wrong time, the patients will have inadequate serum and tissue concentrations of antibiotic at the time of incision and during the surgery. This, in turn, may lead to a greater risk of contamination and SSIs.…”
Section: Discussionmentioning
confidence: 99%